The Comparison of Oprah Shows from The Theory of Conversational Styles and Preference Structure - Sylvia, Sylvia; Dewi, Ienneke Indra (Bina Nusantara University, 2012)
This paper intends to compare the conversational styles and the preference structure between Oprah shows in FRIENDS which is in a group guest and J.K. Rowling in a single guest. The data were taken from two different videos of Oprah transcribed and analysed. In FRIENDS edition, the conversational style is high considerateness style and in J.K. Rowling edition is high involvement style. The conversation in FRIENDS edition is relatively slower than in J.K. Rowling edition. Oprah as the host uses high involvement style in both editions. In FRIENDS edition, the first part of pairs that mostly occurs is question which the second part is expected answer, while J.K. Rowling is assessment which the second part is agreement. It means that they prefer using positive response rather than negative response.